"We give them threatening advice…": expectations of adherence to antiretroviral therapy and their consequences among adolescents living with HIV in rural Malawi. Issue 3 (2nd March 2020) - Burns, Rose; Magalasi, Denview; Blasco, Philippe; Szumilin, Elisabeth; Pasquier, Estelle; Schramm, Birgit; Wringe, Alison
Abstract: Introduction: Many adolescents living with HIV in sub‐Saharan Africa struggle to achieve optimal adherence to antiretroviral therapy (ART), but few studies have investigated how their treatment‐taking decisions are influenced by their social interactions with providers, caregivers and community leaders. This study aims to explore the narratives that define expectations of adherence to ART among adolescents living with HIV in a rural Malawian setting. Methods: Overall, 45 in‐depth interviews were conducted in 2016 with adolescents living with HIV, caregivers, health workers and community leaders, and four group sessions using participatory tools were undertaken with adolescents. Interviews and group sessions were audio‐recorded, transcribed and translated into English. Data were coded inductively and analysed thematically. Results: Adolescents were given strict behavioural codes around optimal treatment adherence, which were often enforced through encouragement, persuasian and threats. In HIV clinics, some staff supported adolescents with broader concerns relating to living with HIV, but other measures to address sub‐optimal adherence in HIV clinics were perceived by patients as punitive, including pill‐counts and increased frequency of clinic visits. Community leaders felt responsible for young peoples' health, sometimes attempting to influence their treatment‐taking by threatening to withdraw services, or to publically "out" those deemed to be non‐adherent. At home, discussions with adolescents about HIV were often limited to dose reminders, and some caretakers resorted to physical punishment to ensure adherence. While some adolescents complied with strictly‐enforced adherence rules, others demonstrated resistance by hiding missed doses, secretly throwing away drugs, or openly refusing to take them. Conclusions: The potential of young people to adhere to their ART may be undermined by restrictive messages and punitive approaches to enforce and control their engagement with treatment at home, in the clinic and in the wider community. Interventions should focus on creating safe spaces for adolescents to speak frankly about the adherence challenges that they face and support for caregivers including home‐based interventions.